2013
DOI: 10.1021/cn400106n
|View full text |Cite
|
Sign up to set email alerts
|

D-512 and D-440 as Novel Multifunctional Dopamine Agonists: Characterization of Neuroprotection Properties and Evaluation of In Vivo Efficacy in a Parkinson’s Disease Animal Model

Abstract: In this Article, we have demonstrated the in vivo efficacy of D-512 and D-440 in a 6-OHDA-induced unilaterally lesioned rat model experiment, a Parkinson's disease animal model. D-512 is a novel highly potent D2/D3 agonist, and D-440 is a novel highly selective D3 agonist. We evaluated the neuroprotective properties of D-512 and D-440 in the dopaminergic MN9D cells. Cotreatment of these two drugs with 6-OHDA and MPP+ significantly attenuated and reversed 6-OHDA-and MPP+-induced toxicity in a dosedependent mann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 53 publications
1
38
0
Order By: Relevance
“…In this regard, we have recently characterized the neuroprotective effects of two lead compounds, D-512 and D-440, via assessment of their effects on neurotoxicity associated with 6-OHDA and MPP + administration in DAergic MN9D cells (Santra et al 2013). We have now begun to further explore the possible mechanisms underlying D-512’s neuroprotective effects in several additional studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we have recently characterized the neuroprotective effects of two lead compounds, D-512 and D-440, via assessment of their effects on neurotoxicity associated with 6-OHDA and MPP + administration in DAergic MN9D cells (Santra et al 2013). We have now begun to further explore the possible mechanisms underlying D-512’s neuroprotective effects in several additional studies.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we have shown that D-512 significantly attenuates 6-OHDA- and MPP + -induced neurotoxicity in dopaminergic MN9D cells in a dose-dependent manner. Inhibition of caspase 3/7 activity and reductions in lipid peroxidation along with restoration of tyrosine hydroxylase levels in 6-OHDA-treated cells may partially explain D-512’s mechanism of action (Santra et al 2013). In this current study, we further explore the neuroprotective effect of D-512 in an alternative cellular model, rat adrenal phaeochromocytoma PC12 cells (a rat pheochromocytoma line), against 6-OHDA-induced cytotoxicity, as well as possible mechanisms involved.…”
Section: Introductionmentioning
confidence: 99%
“…2636 Some of our lead multifunctional D 2 /D 3 agonist molecules, such as ( S )- N 6 -(2-(4-([1,1′-biphenyl]-4-yl)piperazin-1-yl)ethyl)- N 6 -propyl-4,5,6,7-tetrahydrobenzo[ d ]thiazole-2,6-diamine (D-264) and 1 (D-512) (Figure 1), exhibited neuroprotection in in vitro and in vivo experiments. 30,33,34 Additionally, we have reported development of multifunctional brain penetrant iron chelators with agonist activity at D 2 /D 3 receptors. 29,31 …”
Section: Introductionmentioning
confidence: 99%
“…32 As the compound turned out to be a promising candidate for PD through a number of experiments, 33,34 we further wanted to delve into a comprehensive structure−activity relationship (SAR) study and accordingly introduce, in the current work, several indole derivatives on the piperazine ring with varying chain length and position of attachment in the indole aromatic ring. We have also introduced a propargyl group in our core hybrid structure to shed light on its role in interacting with DA D 2 /D 3 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…As of now, no neuroprotective drugs have been identified or approved by the FDA for the treatment of PD. The overall goal of our research is to develop orally active multifunctional treatment agents to address both symptomatic (relieving motor dysfunction) and disease-modifying neuroprotective effects to slow or stop the progression of the disease (Das et al, 2015; Ghosh et al, 2010; Li et al, 2010; Modi et al, 2014; Santra et al, 2013; Shah et al, 2014). A number of iron chelators have been employed in the preclinical and clinical studies of PD (Devos et al, 2014; Grolez et al, 2015).…”
Section: Introductionmentioning
confidence: 99%